A candidate optically quiescent quasar lacking narrow emission lines. Issue 1 (26th February 2021) - Greenwell, Claire; Gandhi, Poshak; Stern, Daniel; Boorman, Peter; Toba, Yoshiki; Lansbury, George; Mainieri, Vincenzo; Desira, Christopher
ABSTRACT: Many active galactic nuclei (AGN) surveys rely on optical emission line signatures for robust source classification. There are, however, examples of luminous AGN candidates lacking such signatures, including those from the narrow-line region, which are expected to be less susceptible to classical nuclear (torus) obscuration. Here, we seek to formalize this subpopulation of AGN with a prototypical candidate, SDSS J075139.06+402810.9. This shows infrared (IR) colours typical for AGN, an optical spectrum dominated by an early type galaxy continuum, an [O iii ] λ5007Å limiting flux about two dex below Type 2 quasars at similar IR power, and a k -corrected 12 μ m quasar-like luminosity of ∼ 10 45 erg s −1 . These characteristics are not consistent with jet and host galaxy dilution. A potential scenario to explain this AGN quiescence in the optical is a sky-covering 'cocoon' of obscuring material, such that the AGN ionizing radiation is unable to escape and excite gas on kpc scales. Alternatively, we may be witnessing the short phase between recent triggering of obscured AGN activity and the subsequent narrow-line excitation. This prototype could define the base properties of an emerging candidate AGN subtype – an intriguing transitional phase in AGN and galaxy evolution.